2005
DOI: 10.1007/s10856-005-0627-8
|View full text |Cite
|
Sign up to set email alerts
|

Salivary bisphenol-A levels detected by ELISA after restoration with composite resin

Abstract: Bisphenol-A diglycidylether methacrylate (Bis-GMA), which is synthesized from bisphenol-A (BPA), a compound with exogenous endocrine disrupter action, is widely used as a dental material. During clinical filling with sealants and composite resins, the compounds are solidified by polymerization and then used. However, it has been noted that unpolymerized monomers may become dissolved in saliva. In this study using a competitive ELISA system, we investigated the changes in the BPA concentration in saliva after r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
91
1
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(100 citation statements)
references
References 22 publications
4
91
1
4
Order By: Relevance
“…More information on bisphenol A concentrations in saliva and urine is included in Section 2, and exposure estimates are provided in Section 1.2.4.1.2. The study authors noted that saliva concentrations detected in their study were B1000 times lower than those reported by Olea et al (1996) but were within the ranges reported by Fung et al (2000) and Sasaki et al (2005). Analytical procedures and use of a large amount of sealant were noted as possible reasons for the higher values reported by Olea et al (1996).…”
Section: Fcpsa (2005)supporting
confidence: 45%
See 1 more Smart Citation
“…More information on bisphenol A concentrations in saliva and urine is included in Section 2, and exposure estimates are provided in Section 1.2.4.1.2. The study authors noted that saliva concentrations detected in their study were B1000 times lower than those reported by Olea et al (1996) but were within the ranges reported by Fung et al (2000) and Sasaki et al (2005). Analytical procedures and use of a large amount of sealant were noted as possible reasons for the higher values reported by Olea et al (1996).…”
Section: Fcpsa (2005)supporting
confidence: 45%
“…The European Union (2003) noted that the concentrations of saliva bisphenol A reported by Fung et al (2000) were 4250 times lower than those reported by Olea et al (1996). Sasaki et al (2005) used ELISA to examine salivary bisphenol A concentrations in 21 patients before and after 1 cavity was filled with 0.1 g of composite resin. The resins consisted of bisphenol A diglycidylether methacrylate (i.e., bis-glycidyldimethacrylate), triethylene glycol dimethacrylate, and/or urethane dimethacrylate.…”
Section: Fcpsa (2005)mentioning
confidence: 99%
“…BISPHENOL A (a) Exposure BPA is used in a variety of consumer products, including epoxy resins that are used to line food cans (Kang et al 2003), polyester -styrene (Factor 1998) and polycarbonate plastics used for baby bottles and other containers (Brede et al 2003). BPA-containing resins and plastics are also used in some dental sealants (Sasaki et al 2005) and fillings ( Joskow et al 2006), adhesives, protective coatings, flame retardants (Samuelsen et al 2001) and water storage tanks and supply pipes (Bae et al 2002). BPA is a polymer, but degrades into its monomeric form over time, a process that can be accelerated by heat exposure (Brotons et al 1995).…”
Section: Phthalates (A) Exposurementioning
confidence: 99%
“…9,10 Conversion is seldom complete 11-14 and lower conversion results in reduced physical properties, 16-20 reduced bond strengths, 20 decreased marginal integrity and increased wear, 21,22 higher permeability, 23 more water sorption 24 and more leaching out of uncured monomers. 25,26 …”
mentioning
confidence: 99%